Characterization, localization and axial distribution of Ca2+ signalling receptors in the rat submandibular salivary gland ducts. - Xu, X (1996)
1. To characterize [Ca2+]i signalling in salivary duct cells a procedure was developed for the rapid preparation and isolation of intralobular ducts, some of which had attached intercalated ducts. The isolated ducts retained agonist-induced Ca2+ signalling after permeabilization with streptolysin O (SLO). 2. The improved cell preparation technique was reflected in the repertoire and intensity of agonist responsiveness of the cells. Measurements of [Ca2+]i in intact cells showed that all agonists previously reported to affect electrolyte transport by the submandibular salivary gland (adrenaline, carbachol, isoprenaline and forskolin) mobilized Ca2+ from internal stores and increased Ca2+ influx across the plasma membrane. 3. The use of the SLO-permeabilized ducts showed that all agonists, including isoprenaline and forskolin, mobilized Ca2+ exclusively from the inositol 1,4,5 trisphosphate (IP3)-sensitive pool. However, in granular ducts only adrenaline mobilized the entire IP3-sensitive pool whereas all other agonists mobilized only part of the pool. 4. All regions of the duct responded to substance P and the luminally secreted agonist ATP. Interestingly, the intercalated duct was most responsive to ATP and demonstrated only a minimal response to all other agonists. The granular region of the same duct and the extralobular duct always responded best to stimulation by adrenaline. 5. The perfused extralobular duct was used to show that adrenaline and carbachol stimulated the duct through the basolateral membrane whereas the receptors for ATP were localized in the luminal membrane of the duct. This suggests the presence of an ATP-dependent positive feedback loop in salivary duct with decreased activity along the ductal tree.